Dipole-induced anomalous top quark couplings at the LHC - Tonero, Alberto [UNESP]; Rosenfeld, Rogério [UNESP] (Amer Physical Soc, 2014)
We consider direct bounds on the coefficients of higher-dimensional top quark dipole operators from their contributions to anomalous top couplings that affect some related processes at the LHC. Several observables are studied. In particular, we incorporate for the first time in this type of analysis the recently measured associated t (t) over barV production, which is currently the only measured direct observable sensitive to the dipole operator involving the hypercharge field. We perform a Bayesian analysis to derive the 1(2)sigma confidence level intervals on these coefficients.